From a Heuristic Point of View : Essays in Honour of Carlo Cellucci - Cozzo, Cesare; Ippoliti, Emiliano (Cambridge Scholars Publishing, 2014)
How do we get new knowledge? Following the maverick tradition in the philosophy of science, Carlo Cellucci gradually came to the conclusion that logic can only fulfill its role in mathematics, science and philosophy if it helps us to answer this question. He argues that mathematical logic is inadequate and that we need a new logic, framed in a naturalistic conception of knowledge and philosophy - the heuristic conception. This path from logic to a naturalistic conception of knowledge and philosophy explains the title.